The mapping of TOEFL scores among EFL students in Aceh - Nurkholish Umar; Usman Kasim; Iskandar Abdul Samad (Universitas Syiah Kuala, 2022)
The purpose of this study was to describe the proficiency level of English for Foreign Language (EFL) students based on their TOEFL scores. The samples for this descriptive quantitative study consisted of 30 English Education Department students from Syiah Kuala University and Ar-Raniry State Islamic University. The scores gathered from the organised TOEFL test were analysed according to the CEFR reference levels to categorise the English proficiency level of the students. The total TOEFL scores gathered showed that, on average, the students placed in the B1 (intermediate) level of English proficiency. Individually, there were four students in the A2 (elementary) level, 15 students in the B1 (intermediate) level, ten students in the B2 (upper intermediate) level, and one student in the C1 (advanced) level of proficiency. Regarding the skills proficiency, on average, the students achieved the B2 (upper intermediate) level in the first section, which was higher than the remaining two sections that averaged on the B1 (intermediate) level. The students’ proficiency levels found in this study showed that, on average, they were able to pass the universities’ TOEFL graduation requirement but still fall short for abroad scholarship admission.